Stocks, flows and emissions of DBDPE in China and its international distribution through products and waste - Kaihui Shen; Li Li; Junzhou Liu; Chengkang Chen; Liu, Jianguo* (Environmental Pollution, 2019)
Decabromodiphenyl ethane (DBDPE) is an alternative to the commercial decabromodiphenyl ether (deca-BDE) mixture but has potentially similar persistence, bioaccumulation potential and toxicity. While it is widely used as a flame retardant in electrical and electronic equipment (EEE) in China, DBDPE could be distributed globally on a large scale with the international trade of EEE emanating from China. Here, we performed a dynamic substance flow analysis to estimate the time-dependent mass flows, stocks and emissions of DBDPE in China, and the global spread of DBDPE originating in China through the international trade of EEE and e-waste. Our analysis indicates that, between 2006 and 2016, ∼230 thousand tonnes (kt) of DBDPE were produced in China; production, use and disposal activities led to the release of 196 tonnes of DBDPE to the environment. By the end of 2016, ∼152 kt of the DBDPE produced resided in in-use products across China. During the period 2000–2016, ∼39 kt of DBDPE were exported from China in EEE products, most of which (>50%) ended up in North America. Based on projected trends of China's DBDPE production, use and EEE exports, we predict that, by 2026, ∼74 and ∼14 kt of DBDPE originating in China will reside in in-use and waste stocks, respectively, in regions other than mainland China, which will act as long-term emission sources of DBDPE worldwide. This study discusses the considerable impact of DBDPE originating in China and distributed globally through the international trade of EEE; this is projected to occur on a large scale in the near future, which necessitates countermeasures.